2016
DOI: 10.1021/acsphotonics.5b00568
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Free, Colloidal, and Plasmonic Silicon Nanocrystals Heavily Doped with Boron

Abstract: Colloidal heavily doped silicon nanocrystals (Si NCs) exhibiting tunable localized surface plasmon resonance (LSPR) are of great interest in cost-effective, solution-processed optoelectronic devices given the abundance and nontoxicity of Si. In this work we show that tunable plasmonic properties and colloidal stability without the use of ligands can be simultaneously obtained for Si NCs heavily doped with boron (B). The heavily B-doped Si NC colloids are found to be stable in air for months, opening up the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 68 publications
3
84
0
2
Order By: Relevance
“…[11] Depending on the size and doping level of the nanostructure, LSPRs from the visible through the terahertz can be reached. [11] Strategies to intentionally add dopant atoms to the crystal of a semiconductor nanostructure have seen rapid progress and various doped semiconductor NCs were synthesized, [8] including phosphorous and boron-doped silicon NCs, [14][15][16] aluminum, germanium, or indium doped zinc oxide, [17] and indium doped tin oxide (ITO) NCs. [9] All these NCs have intense resonances in the mid to near IR due to plasmonic absorption.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Depending on the size and doping level of the nanostructure, LSPRs from the visible through the terahertz can be reached. [11] Strategies to intentionally add dopant atoms to the crystal of a semiconductor nanostructure have seen rapid progress and various doped semiconductor NCs were synthesized, [8] including phosphorous and boron-doped silicon NCs, [14][15][16] aluminum, germanium, or indium doped zinc oxide, [17] and indium doped tin oxide (ITO) NCs. [9] All these NCs have intense resonances in the mid to near IR due to plasmonic absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent Si nanocrystals (SiNCs) are intensively studied for their potential applications in diverse fields, such as optoelectronics, sensing, and medicine [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Some particularly important characteristics of such SiNCs include absolute quantum yield (AQY), stability, luminescence lifetime, surface chemistry, and synthesis route.…”
Section: Introductionmentioning
confidence: 99%
“…For elemental semiconductor NCs such as Si NCs gas‐phase doping has been found to be effective . It has been shown that the structural, electronic, and optical properties of Si NCs can be tuned by doping …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] It has been shown that the structural, electronic, and optical properties of Si NCs can be tuned by doping. [23][24][25][26][27][28] As another type of important elemental semiconductor NCs, Ge NCs hold a unique position because of a series of advantageous materials properties, including strong optical absorption and high mobilities of electronic carriers. [ 29 ] Although Ge NCs can now be controllably synthesized, [30][31][32] the doping of Ge NCs has been rarely explored.…”
mentioning
confidence: 99%